Changes in wheelchair biomechanics within the first 120 minutes of practice: spatiotemporal parameters, handrim forces, motor force, rolling resistance and fore-aft stability. (2nd April 2020) - Eydieux, Nicolas; Hybois, Samuel; Siegel, Alice; Bascou, Joseph; Vaslin, Philippe; Pillet, Hélène; Fodé, Pascale; Sauret, Christophe
Abstract: Purpose: During manual wheelchair (MWC) skill acquisition, users adapt their propulsion technique through changes in biomechanical parameters. This evolution is assumed to be driven towards a more efficient behavior. However, when no specific training protocol is provided to users, little is known about how they spontaneously adapt during overground MWC locomotion. For that purpose, we investigated this biomechanical spontaneous adaptation within the initial phase of low-intensity uninstructed training. Materials and methods: Eighteen novice able-bodied subjects were enrolled to perform 120 min of uninstructed practice with a field MWC, distributed over 4 weeks. Subjects were tested during the very first minutes of the program, and after completion of the entire training protocol. Spatiotemporal parameters, handrim forces, motor force, rolling resistance and fore-aft stability were investigated using an instrumented field wheelchair. Results: Participants rapidly increased linear velocity of the MWC, thanks to a higher propulsive force. This was achieved thanks to higher handrim forces, combined with an improved fraction of effective force for startup but not for propulsion. Despite changes in mechanical actions exerted by the user on the MWC, rolling resistance remained constant but the stability index was noticeably altered. Conclusion: Even if no indication is given, novice MWC users rapidly change their propulsion technique and increase their linear speed. Such improvements in MWC mobility are allowed by a mastering of the whole range of stability offered by the MWC, which raises the issue of safety on the MWC. Implications for rehabilitation: The learning process of manual wheelchair locomotion induces adaptations for novice users, who change their propulsion technique to improve their mobility. Several wheelchair biomechanical parameters change during the learning process, especially wheelchair speed, handrim forces, motor force, rolling resistance and fore-aft stability. Fore-aft stability on the wheelchair rapidly reached the tipping limits for users. Technical solutions that preserve stability but do not hinder mobility have to beimplemented, for instance by adding anti-tipping wheels rather than moving the seat forwards with respect to the rear wheels axle.